Technological applications in public libraries New Roles of Information Specialist in Public Libraries under Web 2.0-You tube- - hadj, Chouaib (Journal of Social Sciences and Humanities, 2020)
The current era is characterized by its technological openness, which has touched many fields and sectors so that it was described as the era of globalization with distinction. Modern technological developments through its methods and applications have brought about radical changes at the level of the work environment of information institutions, as it changed the ideology of jobs and services carried out by these institutions. It also affected the nature of the needs and uses of the audience of beneficiaries. This happened in light of the The current era is characterized by its technological openness, which has touched many fields and sectors so that it was described as the era of globalization with distinction. Modern technological developments through its methods and applications have brought about radical changes at the level of the work environment of information institutions, as it changed the ideology of jobs and services carried out by these institutions. It also affected the nature of the needs and uses of the audience of beneficiaries. This happened in light of the development of web generations, the emergence of online indexes, social networks, the trend towards the publication of digital information sources, and the development of subscription trends in electronic periodicals. With the emergence of trends in the movement of free access to information and other developments, this openness led to the approximation of distances and the acceleration of the effectiveness of the transfer and receipt of information and the transfer of digital space from a rigid space dependent on the receipt of information to a more interactive and dynamic system and the integration of the forum in this interactive process (or what is known as the content industry Digital). Among the real reasons for this interaction is the Web 2.0 in general and social media networks in particular.Accordingly, the idea of this scientific paper came to shed light on the most important techniques and knowledge that the information specialist in public libraries must master in order to guarantee himself a place among these technological changes. the most important roles that he must perform under the web 2.0, and about the most important services that public libraries in Algeria must provide to the beneficiaries in the web 2.0 environment? And how to benefit from the video site you tube social media? Focusing on the experience of private channels to introduce books and book (booktuber) also seeks to identify the most important difficulties and challenges facing the information specialist in the digital environment through this applied study.